Photocatalytic Degradation of Methylene Blue by Graphene Impregnated with CeO2 Nanoparticles under Ultrasonic Irradiation - Min Kim, Young; Hwi Cho, Bum; Bae Ko, Weon (Asian Journal of Chemistry, 2013)
Graphene/CeO2 nanocomposites were synthesized in an erlenmeyer flask from hexadecyl trimethylammonium bromide, ammonium cerium nitrate and graphene. Water and ethanol were added to the mixture and stirred until complete dissolution. After exposing the solution to ultrasonic irradiation for 1 h, the colloid was filtered, washed with distilled water and dried overnight in air. The graphene/CeO2 nanocomposites were calcinated in an electric furnace at 700 ºC for 2 h. The resulting of the heated graphene/CeO2 nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The photocatalytic properties of the heated graphene/CeO2 nanocomposites in the degradation of an organic dye, methylene blue, under ultraviolet light at 254 nm were confirmed by UV-Vis spectrophotometer.